Anatomical parameters of and differences in the proximal femoral cavity in adult patients with developmental hip dysplasia - Ran Zhao; Hong Cai; Hua Tian; Ke Zhang (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the anatomical parameters proximal femoral cavity and developmental dysplasia of the hip. Methods: The retrospective study was conducted at Peking University Third Hospital, Beijing, China, and comprised data of adult patients of either gender who underwent total hip arthroplasty from January 2009 to August 2015. Paients with a diagnosis of primary osteoarthrosis or aseptic necrosis of the femoral head were taken as the control group A, while patients with developmental dysplasia of the hip in group B were graded into subgroups I-IV using the Crowe classification. For each patient, the inner diameter of the proximal femoral medullary cavity was measured on preoperative radiographs using Noble’s technique. Data was analysed using SPSS 20. Results: Of the 835 hips, 571(68.4%) were in group A and 264(31.6%) in group B. The mean age of the patients at the time of surgery was 58.3 ± 12.3 years. Overall, there were 404(48.4%) hips of male patients; 59(22.3%) in group B. There were 431(51.6%) hips of female patients; 205(77.7%) in group B. In group B, 186(70.5%) hips were graded I, 38(14.4%)grade II, 22(8.3%)grade III, and 18(6.8%) hips were graded IV. There were significant differences in femoral offset, height of the femoral head, and canal flare index of the metaphysis between groups A and B (p<0.05). There was no significant difference in the morphology of the marrow cavity between subgroups II and III.